Effect of the quorum‐sensing luxS gene on biofilm formation by Enterococcus faecalis. (15th April 2016) - He, Zhiyan; Liang, Jingping; Zhou, Wei; Xie, Qian; Tang, Zisheng; Ma, Rui; Huang, Zhengwei
Abstract : Enterococcus faecalis is the species of bacterium most frequently isolated from the root canals of teeth that exhibit chronic apical periodontitis refractory to endodontic treatment. In this study, we evaluated the effect of the S‐ribosylhomocysteine lyase ( luxS ) quorum‐sensing gene on E. faecalis biofilm formation by constructing a knockout mutant. The biofilms formed by both E. faecalis and its luxS mutant strain were evaluated using the MTT method. Important parameters that influence biofilm formation, including cell‐surface hydrophobicity and the nutrient content of the growth medium, were also studied. Biofilm structures were observed using confocal laser scanning microscopy (CLSM), and expression of biofilm‐related genes was investigated using RT‐PCR. The results showed that the luxS gene can affect biofilm formation, whereas it does not affect the bacterial growth rate. Deletion of the luxS gene also increased cell‐surface hydrophobicity. Biofilm formation was accelerated by the addition of increasing concentrations of glucose. The CLSM images revealed that the luxS mutant strain tends to aggregate into distinct clusters and relatively dense structures, whereas the wild‐type strain appears confluent and more evenly distributed. All genes examined were up‐regulated in the biofilms formed by the luxS mutant strain. The quorum‐sensing luxS gene can affect E. faecalis biofilm formation.